Effect of surface nanocrystallisation on the microstructure and wear resistance of vacuum carburised alloy. Issue 2 (22nd January 2018) - Dong, Meiling; Cui, Xiufang; Wang, Haidou; Jin, Guo; Cai, Zhaobing; Wei, Youyou; Lu, Bingwen
ABSTRACT: In this work, a nanocrystallisation surface layer with an average grain size of 29 nm was fabricated on the 12Cr2Ni4A steel by the supersonic fine particles bombarding (SFPB). The vacuum carburising process was carried out on the original and the SFPB pre-treatment samples. X-ray diffraction, scanning electron microscopy and hardness tester were employed to study the phase constituents, grain size, hardness and residual stress of the two carburised samples. Experimental results showed that compared to the coarse-grain carburised layer (without SFPB), the carburised layer with SFPB pre-treatment has smaller martensite and carbide, and its thickness, hardness, compressive residual stress and wear resistance have been significantly improved. The dominant wear mechanisms of the two carburised samples were both abrasive wear and fatigue wear.